Experiential Culture Model: An Analysis of Moment Structures Approach Utilizing Small and Medium Enterprises in Eldoret Town, Kenya - Tarus , B. Kipchumba (African Journal of Education,Science and Technology (AJEST), 2020)
Most organizations in the 21st century have not been able to realize their full potential due to avoidance of implementing experiential culture as part of their deliberate strategy and building block for organizational survival in responding to the demands of the competitive markets. Experiences are routes that motivates employees to generate new knowledge resulting into better performances. The paper analyzed the determinants of experiential culture utilizing analysis of moment structures approach (AMOS). Experiential culture is expected to be a determinant of organizational performance however; most organizations have not been incorporating it in their activities resulting in lack of knowledge transfer and performance. The study utilized explanatory research design with stratified and simple random sampling. The model development was guided by Schein (1992) and organizational diagnosis questionnaire of thirty-five scales. Results of the model indicated that experimental culture significantly predicts high performance with (β= 0.48, p < 0.001). Further, the model has three dimensions namely; organizational culture, employee morale and employee development. Lastly, it is expected that organizations should embrace experiential culture in order to realize their full potential.